COVID-19 impacts in Northernmost Finland - Ulla Timlin; Arja Rautio (International Journal of Circumpolar Health)
The COVID-19 pandemic challenged our lives during the years 2020–2022. Impacts could be seen in everyday life, both locally and nationally, through economic, mental and social elements. However, these effects varied depending on the life situation of individuals. This paper aims to gather information from the representatives and operators working in two Finnish municipalities, Inari and Utsjoki, to understand and learn about their experiences during the COVID-19 pandemic. The data (20 interviews) were collected between December 2021 and February 2022 and analysed following the principles of the qualitative content analysis. The results suggest that the effects of COVID-19 emerged through issues related to the national border between Finland and Norway, economic challenges, and the pressure that people experienced. However, despite challenges, people were supported by everyday life and a connection to nature, communality and close co-operation. Additionally, local needs were highlighted among participants. The results provide a deeper understanding about the public health impacts in these Northernmost municipalities and can therefore be utilised in future development work. They also provide relevant information on the experiences of Sámi people, and specific views related to Sámi people can be recognised.